1966
DOI: 10.1002/cber.19660990830
|View full text |Cite
|
Sign up to set email alerts
|

Potentielle Cytostatica, 8. N‐Methyl‐N‐[pentahydroxy‐hexyl]‐hydrazine

Abstract: Drei N-Nitroso-1-methylamino-1-desoxy-zuckeralkohole wurden elektrolytisch zu drei N-Methyl-N-[pentahydroxy-hexyll-hydrazinen reduziert. Die Ermittlung der praparativ gunstigsten Bedingungen durch polarographische Untersuchungen mit der Quecksilbertropfelektrode ergab eine pH-AbhLngigkeit sowohl der Halbstufenpotentiale als auch der Stufenhohen und damit des Reduktionsmechanismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1970
1970

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Polarographic data for 18 pharmaceutically important hydrazine derivatives as a function of pH (1130) and for Nmethyl -Ar -(pentahydroxyhexy 1) hytirazones in electrolysis studies (310) were reported. The reaction between benzenediazonium ion and several hydrazones was followed by polarography (491).…”
Section: Organic Halogenmentioning
confidence: 99%
“…Polarographic data for 18 pharmaceutically important hydrazine derivatives as a function of pH (1130) and for Nmethyl -Ar -(pentahydroxyhexy 1) hytirazones in electrolysis studies (310) were reported. The reaction between benzenediazonium ion and several hydrazones was followed by polarography (491).…”
Section: Organic Halogenmentioning
confidence: 99%